1981
DOI: 10.1063/1.328680
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, structure, optical, and magnetic properties of lanthanide aluminate single crystals (LnMAl11O19)

Abstract: Rare-earth aluminates having the general formula LnMAl11O19 with Ln3+ = La, Pr, Nd, Sm, Eu, Gd, and M2+ = Mg, Ni, Co, Mn, Fe have been synthetized. This paper is devoted to mixed compounds of the series La1−xNdx Mg Al11O19 of which large single crystals have been obtained by the flame fusion method. A full refinement of the pure lanthanum compound (x = 0) having a quasimagnetoplumbite structure has been performed (final R = 0.039). Spectroscopic investigations of the (La, Nd) aluminate have allowed the measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
2

Year Published

1983
1983
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(49 citation statements)
references
References 16 publications
3
43
0
2
Order By: Relevance
“…In contrast, the partial replacement of Al 2 O 3 by AlF 3 facilitated the rapid crystallization of CMAT. As shown in Figure 1b, Figure 1e), which is based on the structural data of the magnetoplumbite, 17 is in good agreement with that of prepared CMAT phosphor. Considering that the sintering and the post-heat treatment at higher than 1500 °C are required for typical solid-state and spray pyrolysis techniques, respectively, it is interesting that the reaction is completed at 1200°C by normally heating (3 °C/min) the mixture of oxide-type precursors for CMAT.…”
Section: Resultssupporting
confidence: 65%
“…In contrast, the partial replacement of Al 2 O 3 by AlF 3 facilitated the rapid crystallization of CMAT. As shown in Figure 1b, Figure 1e), which is based on the structural data of the magnetoplumbite, 17 is in good agreement with that of prepared CMAT phosphor. Considering that the sintering and the post-heat treatment at higher than 1500 °C are required for typical solid-state and spray pyrolysis techniques, respectively, it is interesting that the reaction is completed at 1200°C by normally heating (3 °C/min) the mixture of oxide-type precursors for CMAT.…”
Section: Resultssupporting
confidence: 65%
“…These crystal chemistry characteristics impart the LaMA oxide with very good sintering resistance. [25][26][27][28] Our previous studies have already shown that plasma sprayed LaMA coating exhibited much better thermal cycling performance than YSZ and other new TBC candidate materials [29,30]. These results indicate that LaMA is a good TBC candidate material for higher temperature applications.…”
Section: Introductionsupporting
confidence: 52%
“…Our results suggest that Al(2) cations in LMA may have both the ''central atom'' and ''split atom'' configurations: they are positioned randomly below, above, and on the mirror planes (differing also in the magnitudes of the displacement), according to the diverse cationic configurations in the tetrahedral sites surrounding the Al(2). The experimental observation (6,9), indicating that LMA has the ''central atom'' configuration, seems to be reasonable as an averaged approximation, in spite of its inexactness.…”
Section: The Effect Of Mg Distribution On the Positions Of The Al Ionmentioning
confidence: 87%
“…The outer region II is treated as a polarizable dielectric continuum, while the atomic coordinates of the distorted inner region I are explicitly relaxed using appropriate interatomic potentials. Therefore, we can write the total energy E of the system as [6] in which E is the energy of the inner region and thus a function of the coordinates x (and dipole moments) of the ions solely within the region, E depends solely on the displacements y of the ions within region II, and E (x, y) is due to interaction of regions I and II. Table 2.…”
Section: Defect Energy Calculationmentioning
confidence: 99%